2015
DOI: 10.3390/molecules200917393
|View full text |Cite
|
Sign up to set email alerts
|

Selected Phytochemicals and Culinary Plant Extracts Inhibit Fructose Uptake in Caco-2 Cells

Abstract: Abstract:This study compared the ability of nine culinary plant extracts containing a wide array of phytochemicals to inhibit fructose uptake and then explored the involvement of intestinal fructose transporters and phytochemicals for selected samples. The chemical signature was characterized by high performance liquid chromatography with mass spectrometry. Inhibition of [ 14 C]-fructose uptake was tested by using human intestinal Caco-2 cells. Then, the relative contribution of the two apical-facing intestina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…The ability of culinary plant extracts containing phytochemicals to inhibit fructose transport has also been assessed in Caco-2 cells. Lee et al found that demethoxycurcumin and curcumin from turmeric extracts inhibited fructose transport by GLUT2-and GLUT5-mediated fructose uptake, respectively [110]. Similarly, catechin from guava leaf (Psidium guajava) inhibited GLUT5-mediated fructose uptake, whereas quercetin inhibited both GLUT5-and GLUT2-mediated fructose transport [110].…”
Section: Plant Extracts Inhibitors Of Fructose Transportersmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of culinary plant extracts containing phytochemicals to inhibit fructose transport has also been assessed in Caco-2 cells. Lee et al found that demethoxycurcumin and curcumin from turmeric extracts inhibited fructose transport by GLUT2-and GLUT5-mediated fructose uptake, respectively [110]. Similarly, catechin from guava leaf (Psidium guajava) inhibited GLUT5-mediated fructose uptake, whereas quercetin inhibited both GLUT5-and GLUT2-mediated fructose transport [110].…”
Section: Plant Extracts Inhibitors Of Fructose Transportersmentioning
confidence: 99%
“…Lee et al found that demethoxycurcumin and curcumin from turmeric extracts inhibited fructose transport by GLUT2-and GLUT5-mediated fructose uptake, respectively [110]. Similarly, catechin from guava leaf (Psidium guajava) inhibited GLUT5-mediated fructose uptake, whereas quercetin inhibited both GLUT5-and GLUT2-mediated fructose transport [110]. In addition, the ability of guava leaf and guava fruit extracts to inhibit glucose transport have also been demonstrated by Müller et al in Caco-2 cells and mice (C57BL/6N) [111].…”
Section: Plant Extracts Inhibitors Of Fructose Transportersmentioning
confidence: 99%
“…Additionally, the individual flavonol-glycosides found in the guava extract reported no significant differences compared with the uptake of the whole guava extract into epithelial cells (CaCo-2) [60]. In the same cell line, the inhibition of fructose uptake was also tested by Lee et al [61], who confirmed that catechin and quercetin contributed to the inhibition of glucose transporters. In addition, the enhancement of aqueous guava leaf extract was investigated with regard to glucose uptake in rat clone 9 hepatocytes.…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…Therefore, inhibition of GLUT5 activity using dietary substances could offer an effective method for preventing fructose-induced diseases such as metabolic syndrome, hypertension, obesity, and NAFLD. However, little information is available regarding the food ingredients that could suppress intestinal fructose absorption, except for recent reports on a Eucalyptus globulus leaf extract and certain culinary plant extracts [11,12].…”
mentioning
confidence: 99%